2018
DOI: 10.1002/zaac.201800022
|View full text |Cite
|
Sign up to set email alerts
|

Coordination‐directed and Hydrogen‐bonded Assembly of Supramolecular Architectures Constructed from Diverse Coordination of Linear, Triangular, Tetragonal Pyramid, Trigonal Bipyramid, and Octahedral Mononuclear Units

Abstract: Reaction of a imidazole phenol ligand 4-(imidazlo-1yl)phenol (L) with 3d metal salts afforded four complexes, namely, [Ni(L) 6 ]·(NO 3 ) 2 (1), [Cu(L) 4 (H 2 O)]·(NO 3 ) 2 ·(H 2 O) 5 (2), [Zn(L) 4 (H 2 O)]·(NO 3 ) 2 ·(H 2 O) (3), and [Ag 2 (L) 4 ]·SO 4 (4). All complexes are composed of monomeric units with diverse coordination arrangements and corresponding anions. All the hydroxyl groups of monomeric cations are used as hydrogen-bond donors to form O-H···O hydrogen bonds. However, the coordination habit of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Furthermore, the hydrogen-bond networks can provide hydrogen-bond sites that interact weakly with volatile carbonyl compounds. The characteristics of metal-complex-based hydrogen-bond networks have been investigated for more than two decades (for selected reviews, see refs ; for recent examples, see refs ); nevertheless, the adsorption/desorption properties of volatile carbonyl compounds in such networks have not been explored, except in the case of acetone. Takamizawa et al have measured the adsorption isotherm of acetone in a hydrogen-bond network derived from [Co­(ethylenediamine) 3 ]­Cl 3 . The Beatty group has investigated the desorption of co-crystallized acetone from the crystals of [M­(2,4-pyridine dicarboxylate) 2 ] 2– , where M was Cu or Zn. , Castillo and co-workers have confirmed that a [Cu 2 (μ-adenine) 4 Cl 2 ]­Cl 2 -based hydrogen-bond network can adsorb acetone .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the hydrogen-bond networks can provide hydrogen-bond sites that interact weakly with volatile carbonyl compounds. The characteristics of metal-complex-based hydrogen-bond networks have been investigated for more than two decades (for selected reviews, see refs ; for recent examples, see refs ); nevertheless, the adsorption/desorption properties of volatile carbonyl compounds in such networks have not been explored, except in the case of acetone. Takamizawa et al have measured the adsorption isotherm of acetone in a hydrogen-bond network derived from [Co­(ethylenediamine) 3 ]­Cl 3 . The Beatty group has investigated the desorption of co-crystallized acetone from the crystals of [M­(2,4-pyridine dicarboxylate) 2 ] 2– , where M was Cu or Zn. , Castillo and co-workers have confirmed that a [Cu 2 (μ-adenine) 4 Cl 2 ]­Cl 2 -based hydrogen-bond network can adsorb acetone .…”
Section: Introductionmentioning
confidence: 99%